2012
DOI: 10.3748/wjg.v18.i12.1414
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomelanosis duodeni associated with chronic renal failure

Abstract: Pseudomelanosis duodeni (PD) is a rare dark speckled appearance of the duodenum associated with gastrointestinal bleeding, hypertension, chronic heart failure, chronic renal failure and consumption of different drugs. We report four cases of PD associated with chronic renal failure admitted to the gastroenterology outpatient unit due to epigastric pain, nausea, melena and progressive reduction of hemoglobin index. Gastroduodenal endoscopy revealed erosions in the esophagus and stomach, with no active bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…It has been suggested that melanosis could result from iron deposition in the duodenal mucosa secondary to intramucosal haemorrhage or impairment of luminal iron transport after oral iron supplementation 1 6. This theory is supported by electron microscopy that shows ferrous sulfide in the pigment 7.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It has been suggested that melanosis could result from iron deposition in the duodenal mucosa secondary to intramucosal haemorrhage or impairment of luminal iron transport after oral iron supplementation 1 6. This theory is supported by electron microscopy that shows ferrous sulfide in the pigment 7.…”
Section: Discussionmentioning
confidence: 98%
“…It appears to be more common in women in the sixth to seventh decades of life and has distinctive endoscopic, histopathological and electron microscopic features 1. First described in 1976, it was initially thought to be a form of stored iron 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears to be more common in women in the sixth to seventh decades of life and has distinctive endoscopic, histopathological and electron microscopic features. 1 First described in 1976, it was initially thought to be a form of stored iron. 2 Pseudomelanosis duodeni has also been described in patients with hypertension, chronic renal failure, chronic heart failure and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%